PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA MENTIMETER TERHADAP HASIL BELAJAR MATEMATIKA MATERI PENYAJIAN DATA - Layli Putri; Yuli Mulyawati (STKIP Subang, 2022)
This study aims to determine the effect of the problem based learning model with the aid of the mentimeter on the mathematics learning outcomes of data presentation materials. The type of research used is a quasi-experimental design using a nonequivalent control group design. This research was conducted at the Lawanggintung 1 State Elementary School, Bogor City, Class VA, and VB as the experimental class and the control class. The data from this study were analyzed using microsoft excel 2021. Data collection to obtain student learning outcomes tests was obtained using pretest and posttest. The data analysis technique in this study used the t-test. Based on the results of data analysis from hypothesis testing using the t-test, it was obtained tcount = 4.29258, while ttable at a significant level /2 = 0.025 of 2.00324, then obtained tcount > ttable that is 4.29258 > 2.00324 so Ha is accepted or H0 is rejected. This, there is an effect of the problem based learning model on the mathematics learning outcomes of the fifth grade students of SDN Lawanggintung 1.